2015
DOI: 10.1080/21594937.2015.1017303
|View full text |Cite
|
Sign up to set email alerts
|

Children's outdoor playtime, physical activity, and parental perceptions of the neighbourhood environment

Abstract: The purpose of this study was to examine the association between the hours of outdoor play and objective measures of physical activity and identify the correlates of outdoor playing time in terms of parental perceptions of the neighbourhood environment. Time spent in outdoor play, both on a typical weekday and a typical weekend day, and neighbourhood perceptions, was assessed by parental self-report for 889 students attending grades 5 and 6 in Toronto, Canada (mean age: 10.50 ± 0.72 years). Physical activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 32 publications
(38 reference statements)
2
54
2
2
Order By: Relevance
“…Shaw et al () present data on children's independent mobility from surveys conducted in 1971, 1990 and 2010, but questions relating to parental concerns about safety in the local neighbourhood were available for 2010 only. Nevertheless, Shaw et al () show that parents spontaneously cite concerns about neighbourhood safety in relation to the restrictions they place on their children's independent mobility, and studies continue to demonstrate that parental concerns about safety impinge upon children's play outside the home (e.g., Faulkner et al ).…”
Section: The Demise Of An Active Childhood?mentioning
confidence: 99%
“…Shaw et al () present data on children's independent mobility from surveys conducted in 1971, 1990 and 2010, but questions relating to parental concerns about safety in the local neighbourhood were available for 2010 only. Nevertheless, Shaw et al () show that parents spontaneously cite concerns about neighbourhood safety in relation to the restrictions they place on their children's independent mobility, and studies continue to demonstrate that parental concerns about safety impinge upon children's play outside the home (e.g., Faulkner et al ).…”
Section: The Demise Of An Active Childhood?mentioning
confidence: 99%
“…Faulkner et al [16] found that children who spent two or more hours per day playing outside accumulated 27% more minutes of moderate-to-vigorous physical activity (MVPA) than children who played outside for fewer than 30 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Namun, ada beberapa hal yang mengakibatkan seorang anak tidak mampu memproses kelekatannya pada tempat tertentu. Faktor-faktor yang mengancam kelekatan seorang pada tempat tertentu adalah terjeratnya orang tua dalam perangkat sosial tertentu sehingga mempengaruhi kebebasan anak untuk bergerak [12][13][14], adanya persepsi negatif anak terhadap lingkungan [15] dan faktor lingkungan tempat tinggal yang tidak mendukung [16] serta ketergantungan pada televisi dan digital media [17].…”
Section: Pendahuluanunclassified